Video Games Sales Strategy Effectiveness Among Gamers In Batam City : A Comparative Study of Epic Gamers and Steam - Syaeful Anas Aklani; Muhamad Dody Firmansyah; Suwarno Suwarno; Mangapul Siahaan (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
One type of technological development that occurs is the development in video games. Video games are one way to fill free time and can be played by many people. Many companies are strategizing promotions to players to make players interested in the video games offered. The intention of this study is to determine the marketing strategies carried out by Steam and Epic Games, measure the level of effectiveness of video games marketing strategies carried out by Steam and Epic Games, and to fulfill obligations as one of the students majoring in system information at Batam International University. Data collection techniques begin with compiling a research background and formulating an operational definition of variables. Then, continued by looking for quantitative data by making a questionnaire based on the operational variables which is distributed to residents of Batam city and looking for qualitative data By interview. This research result proves either with quantitave or qualitative method discount promotion offers can affect video games sales. While, sales value, discount price factor, competitors offering discount, and bundle product offering does not affect video games sales.conclusions.